637.DEVELOPMENT OF AN INOVATIVE ONE TIME USE PRODUCT - Meli, Stojmirovska; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
In this paper is developed innovation and improvement of a product that already exists on the market and as such in intensively used by a certain group of consumers. At the same time, the possibility of introducing another advantage was seen. This advantage is on one hand improvement, and on the other hand it is an innovation. Its main feature is disposable. In addition to that feature, the innovative product as a set of creative ideas and resources gets a new form, new design an d new way of use, and is also included in the group of environmentally friendly products that are easily degradable and do not pollute the environment. The purpose of this paper is the idea of developing a one time use product, to be realized in an innovative product that will find its practical uses on the market. The expected results show that the introduction of such a new innovative product is necessary, economically justified and that it will find daily application by the target group of customers.